Removal of methylene blue and malachite green dye using different form of coconut fibre as absorbent - Wong Yee Ching; M.S.R. Senan; N.A. Atiqah (Lifescience Global, 2013)
In this study, coconut fibres are grounded and sieved into the size of 150 μm granular form and filament form of uniform size 2.0 cm for absorption test of methylene blue and malachite green dye in single dye solution were studied. As a result, granular form of coconuts have higher percentage removal dye of methyelene blue and malachite green blue which is 98.3% and 99.0%. This study shows a major approach of turning the agricultural waste to an added value product which is absorbent for wastewater treatment especially in textile industries sector.